Hypoglycemic activity of Capparis ovata desf. var. palaestina zoh. methanol extract (Brazilian Journal of Pharmaceutical Sciences, 2018)
Caper (Capparis ovata Desf. and Capparis spinosa L.) is naturally widespread in Turkey. Traditionally, buds, fruits, seeds and roots of this plant are used as tonic, diuretic, anti-rheumatic, expectorant, antidiabetic, and antifungal. The aim of this study is to evaluate potential hypoglycemic effect of C. ovata var. palaestina extracts in alloxan-induced diabetic mice. For this purpose; diabetic mice were administered with 100, 300, 500 mg/kg (i.p.) doses of methanol extract of bud and fruit. Blood glucose levels were screened 60, 120, 240 and 360 min. after treatment. Furthermore, high resolution mass spectrometry (HRMS) analysis, ABTS and DPPH free radical scavenging activity test, and phenolic and flavonoid compounds analysis of extracts were carried out. The data obtained from in vivo study revealed that fruit-methanol 500 mg/kg (FM3), bud-methanol 300 mg/kg (BM2), bud-methanol 500 mg/kg (BM3) extracts showed significant hypoglycemic activity. All extracts indicated significant antioxidant activity, however bud-methanol (BM) extract demonstrated the most potent antioxidant activity. Moreover high levels of phenolic substances and flavonoids were involved in all extracts, but the highest levels were found in FM extract. HRMS study showed that rutin, quercetin 3-O-glucoside (isoquercitrin) and stachydrine substances had seen in BM extract. The results of this study showed that the C. ovata var. palaestina extracts which, indicate hypoglycemic, antioxidant activities, might provide additional support in diabetes.